a Studi Komparatif Hermeneutika Kontekstual Dan Qira’ah Mubadalah Tentang “Dua Banding Satu” Harta Warisan (Qs Al-Nisa - yusran (UIN Kiai Haji Achmad Siddiq Jember, 2024)
This paper discusses the expression two to one listed in QS al-Nisa>' 11. This paper seeks to record the views of the two figures, namely Abdullah Saeed and Faqihuddin Abdul Kodir, which according to the author, there is a re-reading of religious texts, especially in QS al-Nisa>' 11. This paper uses qualitative research with the type of library research (literature) by referring to primary sources, namely the book Interpreting the Qur'an: Towards a Contemporary Approach and Faqihuddin Abdul Qadir's book entitled Qirā'ah mubādalah. The results of the study show that in understanding inheritance, both of them view that